Iatrogenic popliteus tendon injury during total knee arthroplasty results in decreased knee function two to three years postoperatively - de Simone, Vito (Springer-Verlag, 2012)
PURPOSE: The popliteus tendon is known to play a key role in the stability of the posterolateral corner of the knee. While prior work suggests that isolated sectioning of the popliteus tendon has little consequence for the static stability of the knee following TKA, no studies have evaluated the effect of iatrogenic popliteal tendon injury on patient oriented outcome and knee function following TKA. The aims of this study are (1) to compare patient-oriented outcome scores of patients who suffered an iatrogenic injury to the popliteus tendon with a control group without such an injury and (2) to identify risk factors associated with iatrogenic injury to the popliteus tendon. METHODS: Fifteen patients with an iatrogenic complete transection of the popliteus tendon during TKA were compared to the 666 patients who underwent TKA during the same time period without popliteus tendon injury. RESULTS: Postoperatively, IKS knee scores were similar between the two groups; however, significantly lower IKS function scores were noted in the study group (71 ± 31) compared to the control group (86 ± 19) (p = 0.0036). Iatrogenic popliteal tendon injury was only noted to occur in patients in whom components of size four or smaller were used. CONCLUSIONS: Intraoperative complete section of the popliteus tendon during the performance of TKA results in decreased IKS functional scores two to three years postoperatively. Patients with smaller knees may be at higher risk for this complication.